85.3k views
5 votes
What is the answer and how do you do the following
p2 +14p +24

User GKA
by
4.7k points

2 Answers

2 votes

Answer:(p+2)(p+12)

Step-by-step explanation: factor p2+14p using the AC method

User Kevin Frost
by
5.5k points
5 votes

Answer:

hope that helps

Explanation:

Factoring p2-14p-24

The first term is, p2 its coefficient is 1 .

The middle term is, -14p its coefficient is -14 .

The last term, "the constant", is -24

Step-1 : Multiply the coefficient of the first term by the constant 1 • -24 = -24

Step-2 : Find two factors of -24 whose sum equals the coefficient of the middle term, which is -14 .

-24 + 1 = -23

-12 + 2 = -10

-8 + 3 = -5

-6 + 4 = -2

-4 + 6 = 2

-3 + 8 = 5

-2 + 12 = 10

-1 + 24 = 23

User RJV Kumar
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.